2021
DOI: 10.1021/acs.est.0c08395
|View full text |Cite
|
Sign up to set email alerts
|

Algal Organic Matter Drives Methanogen-Mediated Methylmercury Production in Water from Eutrophic Shallow Lakes

Abstract: Algal blooms bring massive amounts of algal organic matter (AOM) into eutrophic lakes, which influences microbial methylmercury (MeHg) production. However, because of the complexity of AOM and its dynamic changes during algal decomposition, the relationship between AOM and microbial Hg methylators remains poorly understood, which hinders predicting MeHg production and its bioaccumulation in eutrophic shallow lakes. To address that, we explored the impacts of AOM on microbial Hg methylators and MeHg production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…However, it remains to be investigated whether the adsorbed Hg­(II) and β-HgS-like species on algal cells could be utilized for microbial methylation upon deposition to sediments or the aphotic region. Previous studies have shown that the adsorbed Hg­(II) on minerals and sediments could potentially be utilized for microbial methylation. , We also note that Hg­(II) is known to complex with AOM or low-molecular-weight thiols and could enhance its availability to some methylators, such as sulfate-reducing bacteria, but not the iron-reducing bacteria. ,,, Given increasing incidences of algal blooms globally, we suggest that further investigation be performed to differentiate relative contributions of algal Hg­(II) uptake and AOM complexation in affecting Hg­(II) bioavailability and methylation in natural aquatic ecosystems.…”
Section: Environmental Implicationsmentioning
confidence: 79%
See 1 more Smart Citation
“…However, it remains to be investigated whether the adsorbed Hg­(II) and β-HgS-like species on algal cells could be utilized for microbial methylation upon deposition to sediments or the aphotic region. Previous studies have shown that the adsorbed Hg­(II) on minerals and sediments could potentially be utilized for microbial methylation. , We also note that Hg­(II) is known to complex with AOM or low-molecular-weight thiols and could enhance its availability to some methylators, such as sulfate-reducing bacteria, but not the iron-reducing bacteria. ,,, Given increasing incidences of algal blooms globally, we suggest that further investigation be performed to differentiate relative contributions of algal Hg­(II) uptake and AOM complexation in affecting Hg­(II) bioavailability and methylation in natural aquatic ecosystems.…”
Section: Environmental Implicationsmentioning
confidence: 79%
“…68,69 We also note that Hg(II) is known to complex with AOM or low-molecular-weight thiols and could enhance its availability to some methylators, such as sulfate-reducing bacteria, but not the iron-reducing bacteria. 34,35,70,71 Given increasing incidences of algal blooms…”
Section: ■ Environmental Implicationsmentioning
confidence: 99%
“…Similar to the observation in spring (across 17 sites), the DTHg concentration also positively correlated with algal density in autumn (Text S2, Table S6, and Figure S8a), owing to the site-specific anthropogenic input. The MeHg concentration also showed a positive relationship with algal density (Table S6 and Figure S8b), which might be explained by that algal-derived organic matter could promote the in situ methylation of inorganic Hg in water and sediment. , As a result, the % MeHg (0.90–1.08%; Table S6 and Figure S8c) in water did not vary significantly across sites, which could not explain the significantly lower % MeHg in plankton at productive sites.…”
Section: Resultsmentioning
confidence: 95%
“…As a consequence, relationships between transcript abundance and the corresponding process have been commonly assumed but rarely observed in the environment . Although relationships between the abundance of hgc genes and MeHg concentrations have been previously identified, no study has yet demonstrated a quantitative relationship between the expression levels of hgc genes (i.e., hgc transcripts) and Hg II methylation rates in the environment or under laboratory conditions. It is thus uncertain if Hg II methylation rates are constrained by the molecular-level methylation processes mediated by the hgc genes.…”
Section: Introductionmentioning
confidence: 99%